2017
DOI: 10.1002/fsn3.535
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pulsed electric fields and microwave pretreatments on some selected physicochemical properties of oil extracted from black cumin seed

Abstract: Application of novel technologies such as microwave and pulsed electric fields (PEF) might increase the speed and efficiency of oil extraction. In the present research, PEF (3.25 kV/cm electric field intensity and 30 pulse number) and microwave (540 W for 180 s) pretreatments were used to study the process of oil extraction from black cumin (Nigella sativa) seeds. After applying the selected pretreatments, the oil of seeds was extracted with the use of a screw press and the extraction efficiency, refractive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
(42 reference statements)
9
29
0
Order By: Relevance
“…Further decrease in oil extraction efficiency at higher microwave irradiation time and PEF intensity could be explained by more destruction of internal structures of cells and blocking of oil extraction pores/routes. Bakhshabadi et al () demonstrated that application of high PEF intensity may lead to a decrease in oil extraction efficiency which were in agreement with the obtained results of the current study. Increase in screw press rotational speed led to a decrease in oil extraction efficiency possibly due to a reduction in applied pressure onto the seeds which is similar to the data reported by some other researcher groups (Deli, Farah Masturah, Tajul Aris, & Wan Nadiah, ; Evon, Vandenbossche, Pontalier, & Rigal, ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Further decrease in oil extraction efficiency at higher microwave irradiation time and PEF intensity could be explained by more destruction of internal structures of cells and blocking of oil extraction pores/routes. Bakhshabadi et al () demonstrated that application of high PEF intensity may lead to a decrease in oil extraction efficiency which were in agreement with the obtained results of the current study. Increase in screw press rotational speed led to a decrease in oil extraction efficiency possibly due to a reduction in applied pressure onto the seeds which is similar to the data reported by some other researcher groups (Deli, Farah Masturah, Tajul Aris, & Wan Nadiah, ; Evon, Vandenbossche, Pontalier, & Rigal, ).…”
Section: Resultssupporting
confidence: 93%
“…Further decrease in oil extraction efficiency at higher microwave irradiation time and PEF intensity could be explained by more destruction of internal structures of cells and blocking of oil extraction pores/routes. Bakhshabadi et al (2018) demonstrated that application of high PEF intensity may lead to a decrease in oil extraction efficiency which were in agreement with the obtained results of the current study. Increase in screw press rotational TA B L E 2 Analysis of variance (ANOVA) for determined parameters in oil extraction by microwave-PEF pretreatment…”
Section: The Effect Of Microwave-pef Pretreatments On Oil Extractiosupporting
confidence: 93%
See 1 more Smart Citation
“…Eventually, they stated that it's possible to use this process in extracting oil from sunflower seeds in higher scales (Shorstkii et al, 2017). Zeng et al (2010) and Bakhshabadi et al (2018) were some other researchers who had used PEF for oil extraction (Zeng et al, 2010;Bakhshabadi et al, 2018). Researchers showed that application of combined pretreatment of hydrothermal-MW leads to increase in the efficiency of oil extraction (Cortese et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods exist for the extraction of the oil from the raw seeds (Babar et al, 2018). These include the use of: petroleum ether (Mai Lea et al, 2004), hexane (Mai Lea et al, 2004), ethanol (Hosseinzadeh, Tafaghodi, Jalal, & Taghiabad, 2013), hydrodistillation (Benkaci-Ali, Baaliouamer, Meklati, & Chemat, 2007), electric fields/microwave (Bakhshabadi et al, 2017a(Bakhshabadi et al, , 2017b, supercritical carbon dioxide (sCO 2 ) (Machmudah, Shiramizu, Goto, Sasaki, & Hirose, 2005), with cold pressing however, being the most popular (Cheikh-Rouhou et al, 2007). Each of these models has their characteristic advantages but several drawbacks exist, including: the use of toxic and hazardous solvents, low extraction yields, application of heat in some cases which can compromise the integrity of extracts, the use of costly apparatus and time consuming methodologies (Kiralan, Ozkan, Bayrak, & Ramadan, 2014;Soto, Chamy, & Zuniga, 2007).…”
Section: Introductionmentioning
confidence: 99%